“The Pentateuch that the Samaritans Chose” - Hjelm, Ingrid (Dansk Teologisk Tidsskrift, 2015)
“The Pentateuch that the Samaritans Chose”, is the heading of Chapter Seven in Magnar Kartveit’s The Origin of the Samaritans (2009). The heading is highly problematic in regard to both the origin of the Samaritans and the production of biblical texts and books in ancient Palestine. Kartveit’s assumption that the Samaritans “chose one text-type in particular among the different texts available” rests on several old paradigms about Samaritan origins and religion, which badly fit recent evidence from archaeology and epigraphy. A continuous and independent Yahvistic cult in Israel, from at least the Iron Age, a temple on Mt Gerizim from early in the Persian period, and a highly developed temple city on Mt Gerizim in the Hellenistic period, do not sustain paradigms about Samaritans as an “aberrant” branch of Judaism or the Samaritan Pentateuch as an off-shoot of a Jewish pre-Samaritan or proto-Masoretic Pentateuch.